A new arborinane-type triterpenoid glycoside and three known megastigmanes from the roots of Cyathula officinalis K.C.Kuan. (October 2022) - Zhao, Rui; Peng, Cheng; Li, Lei; Li, Xin-Rui; Meng, Chun-Wang; Liu, Juan; Xiong, Liang
Abstract: In this phytochemical study, a novel arborinane-type triterpenoid glycoside (1 ) and three known megastigmanes (2 –4 ) were isolated from the dried roots of Cyathula officinalis K.C.Kuan. The structures of these compounds were elucidated using NMR spectroscopy. This is the first report of arborinane-type triterpenoids in the Amaranthaceae family. Among these known megastigmanes, compound 3 was isolated from the Amaranthaceae family for the first time, while compounds 2 and 4 were first reported from the Cyathula genus. The chemotaxonomic significance of these compounds is discussed. Graphical abstract: Image 1 Highlights: A novel arborinane-type triterpenoid glycoside (1 ) was isolated from Cyathula officinalis. This is the first report of arborinane-type triterpenoids in the Aamaranthaceae family. Three known megastigmanes (2 –4 ) were isolated from C. officinalis. Compound 3 was isolated from the Amaranthaceae family for the first time. Compounds 2 and 4 were isolated from the Cyathula genus for the first time.